2009
DOI: 10.1007/s10826-009-9266-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Sensory Deficits and Externalizing Behaviors in an Urban, Latino Preschool Population

Abstract: This study examined the relationship between sensory deficits and externalizing behavior problems in preschool children. Parents of 179 urban, Latino preschool children completed two parent-report measures, the Short Sensory Profile (SSP), as a checklist for sensory symptoms, and the Achenbach Checklist for Ages 1-5 (CBCL/1-5) to assess externalizing behavior problems. Measures were available in Spanish or English depending on the parent's preference. Correlations were performed between the total sensory defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 46 publications
2
31
0
3
Order By: Relevance
“…The presence of deficits in sensory modulation deficits in the group with OD3R (even in a lesser extent than in RSPD group) was also supported by other studies; Specifically sensory modulations deficits showed correlations with Depression, Generalized Anxiety (Gouze et al 2009) and externalizing problems in preschool children (Gunn et al 2009). Further research is necessary to analyze the prevalence of sensory modulation deficits in patient samples with different diagnoses within the DC:0-3R system.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The presence of deficits in sensory modulation deficits in the group with OD3R (even in a lesser extent than in RSPD group) was also supported by other studies; Specifically sensory modulations deficits showed correlations with Depression, Generalized Anxiety (Gouze et al 2009) and externalizing problems in preschool children (Gunn et al 2009). Further research is necessary to analyze the prevalence of sensory modulation deficits in patient samples with different diagnoses within the DC:0-3R system.…”
Section: Discussionsupporting
confidence: 76%
“…The lack of significant differences in other sensory areas in the current study may be related to sample size and/or the sample origin. Other studies (Gunn et al 2009;McIntosh et al 1999a, b) also observed significant differences in other sensory areas; however, the children who composed the control groups in these studies were not from a clinical sample. Regarding the differences in sensory patterns between the groups of the present study, toddlers in the RSPD group were approximately twice as likely to exhibit extreme scores in the low registration pattern as those in the OD3R group.…”
Section: Discussionmentioning
confidence: 81%
“…Gunn (2008) replicated the SSP in a primarily Hispanic (78.9%) sample from lower income brackets. Using the SSP cut-off scores, Gunn (2008) identified a probable difference in sensory regulation in 22% and a definite difference in sensory regulation in 28.6% of the participants in his study, rates 1.6 and 14.3 times higher, respectively, than those in Dunn's (1999) White, non-Hispanic sample.…”
Section: Introductionmentioning
confidence: 83%
“…Profile: SSP) (McIntosh, Miller, Shyu, & Dunn, 1999) 이 가장 일반적으로 사용되고 있다 (Gouze, Hopkins, LeBailly, & Lavigne, 2009;Gunn et al, 2009) (Teresi, Cross, & Golden, 1989).…”
Section: 과 단축 감각 프로파일(Short Sensoryunclassified